The Influence of Originality, Web Quality, Peer Influence, Hedonic, Functional, Social and Cognitive on Consumer Purchase Intention by Using Virtual Administration Services for Online Shopping - M Ghassani Harahap, Fauzan; Akbar Manaf, Peri (DINASTI RESEARCH, 2025)
Virtual administration (VA) services powered by artificial intelligence have recently gained relevance in academia and industry. Digital platforms are increasingly integrating AI-based virtual admin assistants to support consumers during service interactions and the purchasing process. However, the motivational factors that drive consumers to adopt virtual admin services and their influence on purchase intention remain underexplored in the existing literature. Addressing this research gap, this study proposes a theoretical model based on consumer innovativeness, hedonic motivation theory, and the stimulus-organism-response (SOR) framework to investigate how originality, website quality, peer influence, functional, cognitive, and social motivation shape hedonic experiences and purchase intention in the context of AI-based virtual admin services. Data were collected from online users who had interacted with AI-based virtual admin services for online shopping. Structural equation modeling was used to test the proposed hypotheses. The results revealed that originality, website quality, and peer influence significantly enhance consumers' hedonic motivation. Furthermore, hedonic motivation positively impacts purchase intention. In addition, originality, functional value, cognitive value, website quality, and social motivation exert a direct influence on purchase intention. Peer influence significantly predicts social motivation, which subsequently increases purchase intention, highlighting the role of social perception in digital service adoption. This study contributes to the literature by extending consumer innovation theory to the context of AI-based virtual admin services, emphasizing the psychological (hedonic and cognitive), functional, and social dimensions that shape consumer purchase decisions. Practically, these findings provide strategic insights for e-commerce platforms and service designers to enhance virtual admin interfaces, improve website quality, and encourage social engagement to strengthen purchase intention.